Energy Harvesting Integration with Air Quality Monitoring Systems - Santana, E. S. [UNESP]; Arenas, L. A.O. [UNESP]; Liberado, E. V. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Optimizing energy flow is as crucial as challenging in air quality monitoring systems, particularly when applied in remote regions where reduced maintenance of energy storage components is required. However, the development of energy harvesting technologies and their integration with air quality monitors can be a suitable solution to design self-powered systems with optimum energy storage usage. Hence, this paper presents a basic framework of the elements of air quality monitoring systems and energy harvesting technologies, and briefly discusses their integration through the analysis of applications reported in the literature.
Keywords: air quality; energy harvesting; energy optimization; power manage-ment; self-powered systems